The relationship between triglyceride, cholesterol and lipoprotein levels, and immune responses to hepatitis B vaccine - Guo, Dan; Dai, Jiazhen; Ju, Rong; Zhou, Qifan; Wang, Nenghuan; Wu, Chunhua; Tao, Hui; Jing, Hui; Zhu, Chen; Mao, Jinxian; Xu, Jiayan (Frontiers in Medicine, 2023)
Cholesterol homeostasis disorder and hypertriglyceridemia, as common metabolic conditions, have rarely been reported to affect the immune responses to the hepatitis B vaccine. Our study found that higher high-density lipoprotein (HDL) level showed a significant relationship with positive anti-HBs results (cOR = 1.479, 95% CI: 1.150, 1.901, p = 0.002; aOR = 1.304, 95% CI: 1.006, 1.691, p = 0.045), especially in individuals aged 18- to 40-year-old, female, smoking more than 100 cigarettes in life, and drinking more than 12 times every year. Lower low-density lipoprotein (LDL) level was associated with a negative anti-HBs result among participants aged 18- to 40-year-old, and participants who were obese. Higher level of HDL and lower level of LDL may be protective factors of better immune effect of hepatitis B vaccine. More research should be conducted to investigate the influence of the cholesterol level on the immune responses to the hepatitis B vaccine, and more in-depth research should be performed to uncover the mechanism.